The impact of the peer effect on adolescent drinking behavior: instrumental-variable evidence from China - Liu, Meng; Zhao, Wen-Qing; Zhao, Qi-Ran; Wang, Yu; Li, Shun-Guo (Frontiers in Psychiatry, 2023)
Background: Governments around the world have taken measures to limit adolescent drinking, however, rates are still alarmingly high. However, most of these measures ignore the peer effect of drinking among adolescents. Previous studies have not sufficiently considered the reciprocal relationship between adolescent alcohol consumption and peer alcohol consumption, which may lead to an overestimation of the peer effect and mask underlying issues. Good instrumental variables are powerful but rare tools to address these issues.Objective: This paper aims to correctly estimate the peer effect of drinking on adolescent drinking behavior in China.Owing to the detailed information of household background in the dataset of our survey, we were able to use the drinking behaviors of peers' fathers and their beliefs about the health risks of alcohol as instrumental variables, which are more powerful than school-average instrumental variables. We collected data from the 2017 Health and Nutrition Panel survey, which surveyed 10,772 primary school students from 59 urban migrant and 60 rural public schools.The instrumental variable method estimation revealed that peer drinking significantly influences adolescent drinking behavior, with adolescents who have peers who drink alcohol being 10.5 percentage points (2 stage least square, i.e., 2SLS, full sample estimation) more likely to engage in drinking compared to those without such peers. Furthermore, the effect differs significantly between migrant and rural adolescents.The study found that parental care plays a significant role in the degree of peer effect, with the absence of parental care being a key factor in the presence of the peer effect.